Qualités des dossiers universitaires : analyse d’un programme de formation en enseignement - Léon Harvey; Marie-Hélène Hébert; Catherine Simard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This study presents a reading of academic files of students having completed a bachelor degree in a preschool education and primary teaching curriculum in order to assess the validity and reliability of the underlying grades. The impact of factors such as previous college results, campus of study, year of diploma, gender and age are also investigated. The database is composed of 873 graduated students from the preschool education and primary teaching program, having graduated between 2006 and 2012 from one of the two campuses of the University of Quebec at Rimouski. The results of an exploratory factorial analysis suggest that the grades are not the product of random and arbitrary processes. Student grades according to their records are structured according to factors that, as expected, help measure four groups of connected learning outcomes. The set shows good reliability. Multiple level regressions reveal that past college performance is a good predictor of university mean grade point average (UGPA) with no impact of the university campus or the year of diploma. However, some slight iniquities remain in the UGPA as a function of students’ gender and age, once past academic success has been accounted for.